Independent Side-by-Side Validation and Comparison of 4 Serological Platforms for SARS-CoV-2 Antibody Testing. (16th October 2020) - Jahrsdörfer, Bernd; Kroschel, Joris; Ludwig, Carolin; Corman, Victor Max; Schwarz, Tatjana; Körper, Sixten; Rojewski, Markus; Lotfi, Ramin; Weinstock, Christof; Drosten, Christian; Seifried, Erhard; Stamminger, Thomas; et al.
Abstract: Highly sensitive and specific platforms for the detection of anti–severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies are becoming increasingly important for evaluating potential SARS-CoV-2 convalescent plasma donors, studying the spread of SARS-CoV-2 infections, and identifying individuals with seroconversion. This study provides a comparative validation of 4 anti–SARS-CoV-2 platforms. A unique feature of the study is the use of a representative cohort of convalescent patients with coronavirus disease 2019 and a mild to moderate disease course. All platforms showed significant correlations with a SARS-CoV-2 plaque reduction neutralization test, with highest sensitivities for the Euroimmun and the Roche platforms, suggesting their preferential use for screening persons at increased risk of SARS-CoV-2 infections. Abstract : Four broadly used serological testing platforms for detecting antibodies against severe acute respiratory syndrome coronavirus 2 were evaluated regarding their suitability for screening healthcare staff, potential convalescent plasma donors, and others with mild to moderate courses of coronavirus disease 2019.